Influence of recovery intensity on oxygen demand and repeated sprint performance - Yamagishi, T.; Babraj, J. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: This study aimed to determine effects of recovery intensity (passive, 20%, 30% and 40% VO2peak) on oxygen uptake kinetics, performance and blood lactate accumulation during repeated sprints.